Activated Rice Husk-Based Adsorbents For Chlorophenol Removal And Their Bioregeneration - Khor, Siok Moi (2013)
The objectives of this study are to develop rice husk-based adsorbents activated with different activating agents, namely potassium hydroxide (KRH), nitric acid and methanol (ARH), and ethylenediamine (MRH), and compare their adsorption capacities and bioregeneration efficiencies to remove 4-chlorophenol (4- CP) and 2,4-dichlorophenol (2,4-DCP) from the aqueous solutions with the commercially available powdered activated carbon (PAC). From the adsorption equilibrium studies of 4-CP and 2,4-DCP, the trend of maximum adsorption capacity, qm, among the adsorbents followed KRH > PAC > ARH > MRH and in agreement with the trend of BET surface areas. The equilibrium adsorption data of KRH and PAC were best described by the Langmuir model (R2 > 0.98) while the Freundlich model was suitable to describe the equilibrium adsorption data for MRH and ARH (R2 > 0.99). These observations were confirmed by the values of heterogeneity constant, μ, obtained from the Redlich-Peterson model. It could be concluded that the adsorbent surfaces of MRH and ARH were heterogeneous, while those of the KRH and PAC were homogenous. For the temperature-dependent Temkin and Dubinin-Radushkevich isotherm models, the Dubinin-Radushkevich model was better fitted to the experimental data than the Temkin model.